1980
DOI: 10.1177/030089168006600311
|View full text |Cite
|
Sign up to set email alerts
|

Stage I Melanoma of the Limbs. Immediate versus Delayed Node Dissection

Abstract: 553 patients with stage I malignant melanoma of the limbs entered a prospective randomized clinical trial carried out by the W.H.O. Collaborating Centres for Evaluation of Methods of Diagnosis and Treatment of Melanoma from September 1967 to January 1974. 286 patients were submitted to wide excision of primary and node dissection at the time as appearance of regional lymph node metastases and 267 to wide excision and immediate node dissection. Survival was identical in the 2 groups. Different subsets of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The neck dissection includes nodal levels I-V and a superficial parotidectomy should also be performed if the primary melanoma is located between the zygoma and the mastoid. The groin dissection includes the superficial and deep inguinal nodes and the ilio-obturator nodes [104][105][106][107][108][109][110][111]. Some authors have modified the neck dissection, preserving the submental and submandibular nodes (level I) for nodal metastases in the posterior triangle (level V).…”
Section: Radical Lymph Node Dissectionmentioning
confidence: 99%
“…The neck dissection includes nodal levels I-V and a superficial parotidectomy should also be performed if the primary melanoma is located between the zygoma and the mastoid. The groin dissection includes the superficial and deep inguinal nodes and the ilio-obturator nodes [104][105][106][107][108][109][110][111]. Some authors have modified the neck dissection, preserving the submental and submandibular nodes (level I) for nodal metastases in the posterior triangle (level V).…”
Section: Radical Lymph Node Dissectionmentioning
confidence: 99%
“…As to prophylactic node dissection, many investigators reported the results of the studies of melanoma 20–24 . In squamous‐cell carcinoma some investigators reported the incidence of lymphatic metastasis, 7,25–28 but the low rate of metastasis may make the discussion about prophylactic node dissection needless.…”
Section: Commentsmentioning
confidence: 99%
“…In addition, they argued, there was no clear survival benefit for the small percentage of patients who actually had nodal disease compared with those who underwent delayed lymph node dissection (DLND) after nodal involvement became clinically apparent. 8 Several large, randomized multi-institutional studies failed to demonstrate a clear survival advantage for ELND despite earlier retrospective reports espousing significant benefit.…”
Section: Malignant Melanomamentioning
confidence: 99%